2009
DOI: 10.3113/fai-2009-0093
|View full text |Cite
|
Sign up to set email alerts
|

J. Leonard Goldner Award 2008: Effect of Extracorporeal Shock Wave Therapy on Cultured Tenocytes

Abstract: Background: Little has been reported about the biologic effect of shock waves on human normal or pathologic tendon tissue. We hypothesized that inflammatory cytokine and MMP production would be down-regulated by shock wave stimulation. . IL-6 levels were higher in the diseased tenocytes as compared with normal tenocytes (44.10 ± 16.72 versus 0.21 ± 0.55 ng/ml, (p < 0.05). IL-1 levels in normal cells increased (2.24 ± 5.02 ng/ml to 9.31 ± 6.85 ng/ml) after shock wave treatment (p = 0.04). In diseased tenocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
0
17
1
1
Order By: Relevance
“…Several studies have reported that the application of ESWT on cells obtained from different tissues such as bone, tendon etc. caused a marked elevation in the expression of several cytokines . However, in this in‐vivo study, no statistically significant difference was found, on any of the study days, in the percentage of the periodontal area of both the positive and negative control groups that stained positively for any of the cytokines analyzed (except for TNF‐α), on both compression and tension sides.…”
Section: Discussioncontrasting
confidence: 58%
“…Several studies have reported that the application of ESWT on cells obtained from different tissues such as bone, tendon etc. caused a marked elevation in the expression of several cytokines . However, in this in‐vivo study, no statistically significant difference was found, on any of the study days, in the percentage of the periodontal area of both the positive and negative control groups that stained positively for any of the cytokines analyzed (except for TNF‐α), on both compression and tension sides.…”
Section: Discussioncontrasting
confidence: 58%
“…Reduction of inflammatory cytokines characteristic of the CrCL deficient stifle by ESWT may be responsible for improved limb use . An in vitro study of injured human tenocytes that were harvested and then treated with ESWT confirmed reduced levels of interleukin 6 and metalloproteinases 1, 2, and 13 after ESWT of tendon cells in culture . Alteration of these inflammatory mediators may have contributed to the improvement in lameness.…”
Section: Discussionmentioning
confidence: 97%
“…82 Increased levels of tissue healing factors TGF- β 1 and IGF-I expression have been shown after ESWT in a rat tendinopathy model 83 and a significant decrease in some interleukins 84 and matrix metalloprotienases (MMPs) have been shown after shock-wave treatment on cultured tenocytes. 85 …”
Section: Non-operative Treatmentmentioning
confidence: 99%